2021
DOI: 10.1186/s13148-021-01100-x
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging epigenetics to enhance the efficacy of immunotherapy

Abstract: Background Epigenetic mechanisms regulate chromatin accessibility patterns that govern interaction of transcription machinery with genes and their cis-regulatory elements. Mutations that affect epigenetic mechanisms are common in cancer. Because epigenetic modifications are reversible many anticancer strategies targeting these mechanisms are currently under development and in clinical trials. Main body Here we review evidence suggesting that epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…However, in recent years, considerable research efforts have been devoted to identifying a potential link between these processes in the context of cancer. Current literature confirms that these two phenomena are interconnected and mutually regulate each other [ 79 , 80 ]. Epigenetics can modulate tumor antigen presentation and immune cell functions, therefore impacting tumor development and clinical behavior [ 81 ].…”
Section: CM Epigeneticsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in recent years, considerable research efforts have been devoted to identifying a potential link between these processes in the context of cancer. Current literature confirms that these two phenomena are interconnected and mutually regulate each other [ 79 , 80 ]. Epigenetics can modulate tumor antigen presentation and immune cell functions, therefore impacting tumor development and clinical behavior [ 81 ].…”
Section: CM Epigeneticsmentioning
confidence: 98%
“…This is possible due to the ability of epigenetic therapies to modulate the immune response in tumors [ 269 ]. The mechanisms by which these epi-therapies exert their activity are not fully elucidated, but it has been suggested that they may involve reactivation of ERVs, upregulation of tumor-surface antigens, stimulation of antigen-presenting mechanisms, activation of IFN response pathways, transcriptomic reprogramming of TME cells, or induction of immune checkpoint blockade targets such as PD-1/PD-L1 on both tumor cells and lymphocytes alongside reversal of T cell exhaustion [ 79 ]. The mechanisms underlying these actions are depicted in Figure 3 .…”
Section: Epigenetics-based Therapies For CMmentioning
confidence: 99%
“…Tumors characterized by high EVR expression respond better to CTLA-4 (melanoma) and PD1/PDL-1 inhibitors (renal cell carcinoma). The latest research results connect increased EVR expression in various malignancies, including breast cancer, to increased activation of CD8 + cells [ 6 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Moreover, a large fraction of immunotolerant cancers downregulate HLA as a major mechanism of immune evasion and these will remain out of the radar of this approach [ 70 ]. Complex integration of environments, life-style, and dietary factors could further influence the immune system, via metabolic regulations [ 48 , 61 , 69 , 71 76 ], epigenetics [ 77 80 ], autophagy [ 81 86 ], interaction with hormone signalling [ 87 92 ] and microbiome [ 50 , 93 95 ], thus altering the response to these categories of immunotherapeutic agents. Additional clarifications are demanded on the antigenicity of scDB to induce idiotypic responses and more in general on their safety on patients.…”
Section: Bispecific Antibodies As An Innovative Cancer Immunotherapymentioning
confidence: 99%